Confirmatory analysis of total quality management (TQM) framework in selected buffet restaurants in Metro Manila - Banaag, Jeshua (Animo Repository, 2013)
The purpose of this study is to analyze the quality assurance practices of selected buffet restaurants in Metro Manila and to affirm if these are in line with the Total Quality Management principles. Confirmatory research design was utilized in order to verify if management structures and patterns conform to the TQM framework and to collect relevant qualitative data. The research included an analysis on the current restaurant practices through in-depth interviews with the managers and an empirical short survey conducted for 300 randomly selected respondents. The TQM principles were the primary basis of creating a framework which was broken down to six variables including: leadership and commitment, continuous improvement, employee involvement, training & education, total customer satisfaction, and rewards and recognition. Major findings indicate that overall quality is assured when all the TQM principles are being practiced in order to fulfill the dimensions of quality which were identified as the most explicit needs of the customers. Moreover, results revealed that consistency in terms of both food and services was the priority of all the selected buffet restaurants, parallel to the primary concern of the customers. Ultimately, the consolidated quality framework confirmed that the TQM principles are in line with the management practices of the selected buffet restaurant in Metro Manila.